2009
DOI: 10.1007/s10886-009-9600-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Nutritional, and Biochemical Bases of Corn Resistance to Foliage-Feeding Fall Armyworm

Abstract: Three corn (Zea mays) germplasm lines [i.e., Ab24E (susceptible control), Mp708 (resistant control), and a locally selected partial inbred line FAW7050 (resistant)] were examined for Spodoptera frugiperda (J.E. Smith; Lepidoptera: Noctuidae) resistance. Nutritional [i.e., total protein content, amino acids, glucose, total nonstructural carbohydrates (TNC), protein to TNC (P/C) ratios] and biochemical (i.e., peroxidase and lipoxygenase 3) properties in the seedlings of these corn lines were examined to categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 42 publications
6
57
0
1
Order By: Relevance
“…Total nitrogen varied from 2.27 to 3.47 (percentage of dry weight). Chen et al (2009), evaluating leaves of different maize germplasm lines, reported leaf chlorophyll (µmol m −2 ) from 522.56 to 610.37; total protein (mg g −1 of fresh weight of leaf tissue) from 5.74 to 11.12; amino acids (µmol g −1 of fresh weight of leaf tissue) from 6.43 to 11.0; glucose (µmol g −1 of fresh weight of leaf tissue) from 6.39 to 17.26; total nonstructural carbohydrate as the sum of glucose and starch (equivalents of glucose) (µmol g −1 of fresh weight of leaf tissue) from 24.25 to 27.94 and the relationship of protein/carbohydrate (w/w) from 1.27 to 2.69. However, nutrient availability to insects is frequently variable.…”
Section: Discussionmentioning
confidence: 99%
“…Total nitrogen varied from 2.27 to 3.47 (percentage of dry weight). Chen et al (2009), evaluating leaves of different maize germplasm lines, reported leaf chlorophyll (µmol m −2 ) from 522.56 to 610.37; total protein (mg g −1 of fresh weight of leaf tissue) from 5.74 to 11.12; amino acids (µmol g −1 of fresh weight of leaf tissue) from 6.43 to 11.0; glucose (µmol g −1 of fresh weight of leaf tissue) from 6.39 to 17.26; total nonstructural carbohydrate as the sum of glucose and starch (equivalents of glucose) (µmol g −1 of fresh weight of leaf tissue) from 24.25 to 27.94 and the relationship of protein/carbohydrate (w/w) from 1.27 to 2.69. However, nutrient availability to insects is frequently variable.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirm those of Taggar et al (2012) and Taggar et al (2014) who found that B. tabaci feeding in black gram cultivars, increased peroxidase activity and tannin content in the genotypes. Production of phenoxy and other oxidative radicals by the PODs, acting together with phenols such as tannins, have been reported to directly deter the feeding by insects and/or produce toxins that reduce the plant digestibility, which leads to nutrient deficiency in insects with drastic effects on their growth and development (Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…65 Immuno-labeling GNA assay has shown its presence in the fat bodies, ovarioles, and hemolymph, indicating the ability of GNA to cross the midgut that a wide spectrum of PRPs is involved in plant defense against herbivores. 56,57 Due to diverse feeding habits of arthropods, multiple signaling pathways including jasmonic acid (JA), SA and/or ethylene (ET) regulate arthropod-inducible proteins. 8 Plant lectins.…”
mentioning
confidence: 99%
“…Induction of antioxidative enzymes in plants following herbivory has received considerable attention in recent years. [4][5][6][55][56][57][58][59] epithelial barrier and pass into the insect's circulatory system leading to systemic toxic effect. 65 Partial resistance to homopteran insect pests has been reported in transgenic plants expressing snowdrop lectin in tobacco, 66 rice, 67 and wheat.…”
mentioning
confidence: 99%